Process-structure-function relationship for mamaku suspension: Effect of drying methods on powder functionality - Bisht A; Goh KKT; Matia-Merino L (Elsevier Ltd., 2023)
The pith from mamaku tree fern entraps a unique shear-thickening biomacromolecule called mamaku polysaccharide (MP) that may alter the rheological profile in the gut. Here we examined the potential of using the whole pith—natural entrapment of MP in the tissue of pith—to develop a food ingredient with shear-thickening behaviour as an alternative to MP extract. In this study, fresh mamaku pith was collected and dried using an oven-dryer or freeze-dryer, and ground into a powder (ODP: oven-dried powder; FDP: freeze-dried powder). Both the ODP and FDP were characterised for their physical properties (colour, densities, surface morphology), rehydration in water, rheological behaviour and in vitro starch digestion. Freeze-drying resulted in a porous structure, while after oven-drying, the structure collapsed and an increase in density was observed. Upon rehydration with water, both FDP and ODP absorbed water, causing the powder particles to swell and release the water-soluble compounds into the continuous phase. The ability of FDP to release water-soluble MP into the continuous phase resulted in a rheological behaviour of a suspension similar to MP extract solution (shear-thickening behaviour). No shear-thickening was observed in ODP suspension because not enough MP was available in the continuous phase to form polymer-polymer interactions. In-vitro digestion of wheat biscuits mixed with rehydrated FDP suspension reduced starch digestion by ∼35% after 10 min, but starch digestion was unaffected by ODP suspension. This was due to the changes in the rheological behaviour resulting from the alteration in structural characteristics of the powder samples by the different drying methods.
Keywords: Mamaku tree fern pith; Shear-thickening polymer; Freeze-drying and oven-drying; Powder rehydration behaviour; In vitro digestion